Kết quả hiệu chuẩn và xác định hệ số khuếch đại của thiết bị ghi địa chấn tại các trạm địa chấn Việt Nam - Lư, Ngô Thị (Vietnam Journal of Earth Sciences, 2008)
Results of the calibration and determinations of amplification factor of recording equipments at seismic stations of Vietnam